Variability in Wheelchair Propulsion: A New Window into an Old Problem - Sosnoff, Jacob J.; Rice, Ian M.; Hsiao-Wecksler, Elizabeth T.; Hsu, Iris M. K.; Jayaraman, Chandrasekaran; Moon, Yaejin (Frontiers in Bioengineering and Biotechnology, 2015)
Manual wheelchair users(MWU) are at great risk for the development of upper extremity injury and pain. Any loss of upper limb function adversely impacts the independence and mobility of MWU. Motor behavior research suggests that fluctuations in movement(i.e. motor variability) are related to musculoskeletal pain, however few have examined its impact in MWU. This review paper reports on several investigations examining the association between variability in wheelchair propulsion and shoulder pain. These investigations suggest that variability of wheelchair propulsion may be a marker of shoulder pain in MWU. We maintain that these metrics should be included in future research on upper limb pain in MWU. Several promising avenues for future research based on this collective work are discussed.